바이오필름 반응기상에서 수소 이용성 독립영양생물을 이용한 고농도 탈질 반응 - 박대원; 김동건; 박호일; 김지성 (한국물환경학회, 2004)
Autohydrogenotrophic denitrification of high nitrate concentration contaminated wastewater in a batch-scale biofilm reactor has been investigated. High nitrate concentration decreased as pH increased from 7.01 to 9.45. The high nitrate concentrations continuously decrease from 150mg.l-1 to 0mg.l-1. Nitrite concentrations increase at about two-thirds way through the denitrification process and thereafter it decreases with time.Autohydrogenotrophic denitrification of high nitrate concentration is passible to use drinking water as well as wastewater, and to deal with wastewater treatment by hetrotrophic denitrification.